The thermodynamic behavior investigation of adsorption mechanism for removal of cationic dyestuff by hazelnut shell biomass - ÖZVEREN, UĞUR (My University, 2021)
Hazelnut shells, which were crushed in size by pulverization, were used as a bio-based adsorbent for studies on the removal of methylene blue (MB) dye from an aqueous solution. The effects of different operating parameters on adsorption were examined. The adsorbent showed high adsorption efficiency in a wide range of pH and temperature conditions. Furthermore, the Langmuir isotherm results are well-matched with the behavior of the adsorption process. The thermodynamic studies showed that the removal mechanism of MB dye was applicable and occurred spontaneously. The adsorption of MB dye on the adsorbent surface was confirmed by the structural and morphological analysis of the adsorbent before and after adsorption. This study showed that the hazelnut shell adsorbent could be considered as an ideal candidate for the removal of cationic dye pollutants from aqueous
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG); Adsorption; Hazelnut Shell; Methylene Blue Dye; Wastewater Treatment